OPTIMIZATION MODELS FOR COMMUNICATION NETWORK DESIGN - Iryanto et al. (Proceedings of ICMSA, 2005)
The use of both Genetic Algorithms and Linier programming to solvethe general problem of communication system design is considered.The network synthesis problem is known to be NP-complete and thecombinatorial nature of it lends itself to genetic algorithms rather thanconventional mathematical programming approaches. Once a networktopology is established, linier programming can be used to optimizenetwork flows to satisfy specified origin-destination demands.Keywords: Network Design, Genetic Algorithms